Análise de determinantes da satisfação dos alunos da Universidade Pedagógica : delegação de Tete - Augusto, Moisés André (2017)
Project Work presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research e CRM